Industrial trainees learning experiences of English related tasks at the workplace - Amreet Kaur Jageer Singh; Raja Nor Safinas Raja Harun (Studies in English Language and Education, 2020)
This study aims to examine (a) the needs and usage of English language by Industrial Trainees at their workplace, (b) the challenges they faced, and (c) the relevance of Diploma in English courses in a public university in Malaysia to their language and communication needs at the workplace. The sample consists of 55 final year Diploma in English students who had just completed their three months of industrial training at various organisations. The data was collected by means of a questionnaire and semi-structured interviews. The findings of the study indicated that English was widely used in the organisations and all the four language skills were required in conducting various tasks at the workplace. However, most of the trainees experienced difficulty in making online ticketing and online hotel reservations, holding briefings, attending to clients’ concerns and complaints, negotiating with clients to make a deal, making oral presentations, contacting with other firms, preparing the filing system, preparing flyers/brochures/posters/advertisements and preparing accounts. It is thus suggested that the essential courses especially concerning public speaking and interpersonal communication skills to be taught before the students underwent their internship. The findings of the study have some pedagogical implications. Higher education institutions that offer similar courses can make use of these findings in revising the program in line with current demands of education and the workforce. Besides, the lecturers can also rethink the way how specific courses should be taught to meet the students’ needs and allow them to explore meaningful learning through experiential learning.